HUBUNGAN ANTARA KUALITAS LAYANAN DENGAN KEPUASAN KONSUMEN DI RUMAH CANTIK AMANIE KEBUN TEBENG KOTA BENGKULU - Regita Cahyani; Riskan Riskan; Suardi Jasma (Jurnal Pendidikan Sepanjang Hayat, 2019)
This study was aimed to figure out if there is significant correlation between service quality and customers' satisfaction at Rumah Cantik Amanie in Kebun Tebeng of Bengkulu municipality. This was a quantitative study. Method used in this study was survey. Data collection was done by giving away questionnaire in the form of written statement to be filled in by the respondents based on the real situation. The respondents were 212 people, taken by purposive sampling technique. Data analysis method used were descriptive analysis and correlation analysis. Based on the analysis result and hipothesis examination it could be concluded that: (1) Amanie salon's service quality had been quality in the customers'  opinion proven by average score of 4.04. This  average score was in the range of 3.41 - 4.20 which was categorized to be "quality"; (2) Amanie salon's customers' satisfaction had already been satisfied category, with average answer of 4.09. This score was in the range of 3.41-4.20 which meant "satisfied"; (3) There was correlation between service quality and Amanie salon's customers' satisfaction with correlation coefficent of 0.977.  The capability of service quality variable in explaining the rise and fall of Amanie Salon's customers' satisfaction was still huge. It was 95.45%, while the rest 4.55% was affected by other factor which was not studied. Keywords : service quality, customers' satisfaction